Novel exproprioceptive sensor configurations and user interfaces for mobile robot control in uncertain environments - Hau, Chee Seng. (2012)
Modern mobile robots are equipped with numerous sensors for proprioception (monitoring internal state) and exteroception (detecting environment state). However, little work has been done on exproprioceptive sensors, which that detect the pose of a mobile robot relative to its environment.